RELATION OF STRESS-STRAIN STATE IN THE KINEMATIC CHAIN “HIP-AND-KNEE JOINT” WITH THE CERVICAL DIAPHYSEAL ANGLE CHANGING UNDER THE CONDITIONS OF DYSPLASIA - Zelenetsky, I.B.; Miteleva, Z.M.; Snisarenko, P.I.; Jaresko, A.V. (World of Medicine and Biology, 2020)
The article presents the study of biomechanical disorders in the dysplastic process in the hip and knee joints using the finite elements model with different cervical-diaphyseal angles (CDA) of the proximal femoral bone. With the CDA equal to 90°, the femoral neck stress was 42.4 MPa (27.6 in the norm). In the proximal tibia, the level of the stress condition has increased on the medial side up to 17.9 MPa (11.1 normal), and on the lateral side 9.1 MPa (3.5 normal). Thus, on the medial side the stress magnitude is 21.6 MPa (11.2 normal), on the lateral side - 1.7 MPa (2 in the norm). For the CDA equal to 160° the stress in the hip joint reaches 26.5 MPa (27.6 normal). In the proximal tibia on the medial side the tension is 9 MPa (11.1 normal), and on the lateral side it is 3.5 MPa (3.5 normal). Distribution of the stress condition in the knee joint showed that on the medial side the stress magnitude is 13.1 MPa (11.2 normal), and on the lateral side - 3.8 MPa (2 normal). Comparative analysis of the calculations performed for models with different CDA showed that the CDA reduction leads to a significant increase in the stress condition not only in the neck of the femoral bone, but also in the knee joint. Whereas, with increasing CDA the growth of stress-strain state is slight, mainly in the lateral part of the knee joint.